A Systematic Review of Skeletal, Dental and Soft Tissue Treatment Effects of Twin Block Appliance - Daokar, Suchita; Sharma, Mitali (Orthodontic Journal of Nepal, 2020)
This systematic review aims to assess skeletal, dental and soft tissue treatment effects of the conventional Twin-block appliance compared to control in Class II malocclusion till date. The electronic databases of Medline, PubMed and Cochrane library were systematically searched until September 2019. The human studies that had used the conventional Twin block appliance with a control group evaluated by a Lateral Cephalogram were included. A total of 321 articles were examined. 10 articles were selected. Majority studies reported a significant improvement in the mandible and in the vertical height, maxillary restrictive effect was less consistently reported. A restrictive maxillary molar effect and an advancement in the mandibular molar has been suggested. Retroclination of the maxillary incisors and proclination of mandibular incisor inclination has been reported. There is some evidence to suggest a retrusive upper lip effect and a protrusive lower lip effect. Increase in Nasolabial angle and some decrease in the mentolabial sulcus to be expected. In conclusion the conventional Twin Block appliance have shown desirable skeletal, dental and soft tissue effects. However certain inevitable side effects are also seen mainly its effect on lower anterior proclination.